Art therapy toward children with autism spectrum disorder in Kota Kinabalu, Sabah, Malaysia - Naldo Janius; Mohammad Aniq Amdan; Mohd Salehudin Marji; Mohamad Izzuan Mohd Ishar; Nur Firzana Rosman; Vennyssa Anak Anthony; Faizul Hafizzie Dasuki (International Journal of Evaluation and Research in Education (IJERE), 2026)
Autism spectrum disorder (ASD) is a neurodevelopmental condition that presents persistent challenges in communication, emotional regulation, and social interaction. Art therapy has emerged as a promising complementary approach that enables children to externalize emotions, foster creativity, and build social connections. This study is to identify the effectiveness of structured art therapy interventions in enhancing communication, emotional regulation, and social skills among children with ASD. The 10 children aged 4 to 6 years were purposefully selected in structured art therapy sessions for 3 weeks, which were facilitated by five experienced teachers with over 20 years of services (1 teacher: 2 children’s). Data collection employed the behavioral and emotional rating scale‑2 (BERS-2), artwork analysis using the visual emotional and social coding framework (VESCF), and semi‑structured interviews. Quantitative data were analyzed using descriptive statistics, correlations, analysis of variance (ANOVA), and regression, while qualitative data underwent thematic coding with NVivo, ensuring triangulation. Findings revealed significant improvements across communication, social interaction, and daily living skills, with mean scores more than doubling post‑intervention. Studies should be integrated as a complementary intervention alongside traditional therapies, with larger longitudinal studies needed to validate outcomes and support policy integration into early childhood programs.